Glimpses From The Service History Of Officers Of The Surkhandarya Regional Internal Affairs Bodies (Eurasian Journal of Humanities and Social Sciences, 2026)
This article presents a historical and analytical study of the service activities of several officers who have served within the system of the Internal Affairs Bodies of Surkhandarya Region during the years of Uzbekistan’s independence. The research analyzes the professional careers of officers working in criminal investigation, crime prevention, public safety, and road traffic safety sectors. The findings demonstrate the consistent development of personnel training and leadership formation systems within the internal affairs bodies and reveal that the professional experience of officers has become one of the key factors in maintaining law and order in the region